2008
DOI: 10.1016/s1808-8694(15)30607-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Non-embolized Patients with Nasoangiofibroma

Abstract: Resection of JNF types I-III was safely completed in non-embolized patients. The observed levels of intraoperative bleeding, occurrence of complications, and rates of recurrence were close to those seen in embolized patients as found in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
0
21
0
2
Order By: Relevance
“…Petruson et al did not encounter statistically significant differences between intraoperative bleeding in embolized and nonembolized patients [14,16] and found higher JNA relapse rates among embolized patients. Mc Combe et al suggested that preoperative embolization may compromise the identification of surgical margins as it reduces tumor size, consequently increasing chances of relapse [14,17]. Embolization can lead to difficulty in achieving plane of dissection by increasing the fibrous component of the tumor [18].…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Petruson et al did not encounter statistically significant differences between intraoperative bleeding in embolized and nonembolized patients [14,16] and found higher JNA relapse rates among embolized patients. Mc Combe et al suggested that preoperative embolization may compromise the identification of surgical margins as it reduces tumor size, consequently increasing chances of relapse [14,17]. Embolization can lead to difficulty in achieving plane of dissection by increasing the fibrous component of the tumor [18].…”
Section: Discussionmentioning
confidence: 93%
“…Many studies have stated the benefits of preoperative arterial embolization in controlling as much as 50 % of intraoperative bleeding and reduced complications when associated with the endoscopic approach alone [1,[10][11][12][13][14]. However, Preoperative embolization can be avoided in small tumors in contrary to the common belief that it is indispensable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations